USE SOCIAL MEDIA WISELY IN ACCORDANCE WITH APPLICABLE PROVISIONS - Umar, Santoso Budi Nursal; Rahmat, Doris (Universitas Negeri Medan, 2024)
Social media has become an integral part of everyday life, opening up unprecedented opportunities for communication, collaboration and information exchange. However, with the freedom offered by these platforms also comes the great responsibility to use them wisely and in accordance with applicableregulations. This research aims to explore wise practices in the use of social media and their impact on individuals and society. Through a qualitative approach, data was collected through in-depth interviews and observations of various social media users. The research results show that awareness of privacy, diversity ofopinions, control of posted information, and openness to other people's perspectives are important factors in using social media wisely. Apart from that, this researchalso identifies the challenges and obstacles faced in efforts to make social media a positive communication tool. These findings provide valuable insights forindividuals, institutions, and regulators to develop policies and practices that promote responsible and ethical use of social media. . From the research results, itappears that social media users have varying levels of awareness of the terms of use, but compliance with these rules can vary depending on factors such aspeer pressure, the complexity of the rules, and the influence of the social and cultural environment. Challenges in practicing wise use of social media are alsoapparent, ranging from the pressure to maintain a perfect image to the difficulty in distinguishing between valid information and hoaxes. In addition, the positive impacts of social media, such as social connectivity and access to information, are also accompanied by negative risks, including the spread of hoaxes and mental stress. The influence of the social and cultural environment on social media usage practices reinforces the importance of taking into account an individual's social and cultural context in developing appropriate approaches to managing risks and maximizing the benefits of social media. In this context,awareness of the positive and negative impacts of social media is key to helping individuals and society develop more responsible and ethical practices in the use of these platforms. A holistic approach is needed that combines education, social support, and supportive policies to create a healthy and productive onlineenvironment for all users